Using an adaptive, codesign approach to strengthen clinic-level immunisation services in Khayelitsha, Western Cape Province, South Africa - Margaret Kelaher; Ross Stewart Bailie; Andrea Timothy; David Coetzee; Margie Danchin (BMJ Global Health)
Introduction Optimal immunisation programme service delivery and childhood vaccine coverage remains an ongoing challenge in South Africa. Previous health systems approaches have made recommendations on how to address identified barriers but detailed local implementation studies are lacking. This study aimed to improve immunisation service delivery in children under 24 months in Khayelitsha, Western Cape Province using an adaptive, co-design approach to assess and improve childhood immunisation service delivery at the clinic level.Methods A rapid, adaptive approach to identification of barriers and assessment of current childhood immunisation service delivery was developed with three clinics in Khayelitsha, Western Cape Province. This informed a short co-design process with key stakeholders and service providers to develop local interventions targeted at high priority barriers. Interventions were implemented for 4–6 months and evaluated using theory-based evaluation tools. Clinic service delivery, satisfaction and changes to clinic processes and parent engagement and knowledge were measured.Results Interventions developed included weekly community immunisation education radio sessions, daily clinic health talks, immunisation education and promotion materials and service provider and parent quality checklists. Evaluation post-intervention showed improvement in parents’/guardians’ knowledge about immunisation, parent engagement and service provider commitment to improvement in service quality. Radio sessions and immunisation education and communication materials were deemed most useful by parents and providers.Conclusion Immunisation service delivery can be strengthened using an adaptive, clinic-led assessment process which can effectively identify barriers, inform co-designed interventions and be evaluated over a short period. This approach provides a framework to guide future local participatory action research to more effectively improve childhood immunisation service delivery and other child health services in under-resourced settings.